WHITE COLOR IN THE LYRICS OF HALIMA KHUDOYBERDIEVA (Scientific journal of the Fergana State University, 2026)
The article discusses the artistic and aesthetic significance of the use of white color in the lyrics of Halima Khudoyberdiyeva. The expressiveness of the poet's poetry is studied as a phenomenon that arose at the core of the mastery of the artistic and ideological use of color. The way in which a color, which has been an adjective for various concepts, expresses a creative idea through its juxtaposition or contrast with itself is analyzed. This is shown on the example of the most actively used white color in the poet's work.